IMPLEMENTASI AKAD MUKHABARAH DALAM PRAKTEK TESANG GALUNG - Wahyuni (Mappideceng:Jurnal Ekonomi Syariah, 2024)
This jurnal discusses the Implementation of Mukhabarah Contracts in the practice of Tesang Galung in Massewae Village, Duampanua Pinrang District. The purpose of this thesis research is to find out the muzara'ah and mukhabarah contracts in the practice of tesang galung which are based on the form of cooperation between land owners, third parties and managers. The practice carried out by the people of Massewae Village, Duampanua District, is in this tesang galung practice to see the implementation of the muzara'ah and mukhabarah contracts in a system that has blended in with custom.                     This type of research is qualitative where this research links several parties in it, by directly meeting sources of information in the field, namely the community who practice the tesang galung. The methods used are interviews, observation, documentation. Followed by data analysis to the validity of the existing data in the field.                     The results of this study are: first, the existing system in the practice of tesang galung includes the form of cooperation and profit sharing between the land owner and cultivator where this form of cooperation is carried out by two parties between the land owner and the second is the implementation, where when the land owner If the cultivator is given to manage their land, then the land owner fully surrenders and will receive profit sharing. And thirdly, the muamalah activity of the tesang galung practice carried out by the people of Massewae Village, Duaampanua Pinrang District, if it is associated with the muzara'ah and mukhabarah contracts, it is clear that this has not been implemented properly, however, there are some who have implemented muzara'ah and forms of cooperation from the tesang galung practice, more closely following the customary system that has blended in with the people of Massewae Village, Duampanua Pinrang District. Because they think that it is fair for them for some people.